Methodological variations in art research: hybrid heuristics - Oliveira, Valdemir de; Minuzzi, Reinilda de Fátima Berguenmayer (Farol, 2024)
This text seeks possible answers to the question of what research in visual poetics can be. Articulating reflections based on the conceptions of hybrid heuristics proposed by Agnus Valente (2015), it analyzes and discusses operative procedures in the field of artistic research involving creative processes. Authors such as Sandra Rey (2002) and Icleia Cattani (2002) are used to collaborate with the proposed reflections. Finally, it is considered that the contributions of the author in question to the field of art research, with regard to hybrid heuristic processes, broadens, makes more flexible and offers alternatives for thinking and doing research in the artistic field using procedures that are consistent with the unique nature of the area, in addition to traditional methodologies.
Keywords: Visual poetcs; Heuristic Hibrid; Cretive process; Methodology; Art